Quality of life in adolescents with inflammatory bowel disease: a systematic review of the literature - Lopes, Rosa Cristina Correia (2014)
Inflammatory bowel disease is a chronic disease that occurs frequently in adolescence and its incidence is increasing. Adolescence is a transition period marked by change course and physical, psychological and social adjustment. The adolescent not only has to adapt to a new physical condition, often seen as limiting, but also manage the disease and its symptoms with your family, social and school environment. This study aims to analyse the impact of inflammatory bowel disease in adolescents in all its dimensions. Was used as the research methodology Systematic Review of the Literature and the research was conducted in the search engine b-on. The research question was prepared by the method of PI[C]OD - What is the impact of inflammatory bowel disease on quality of life of adolescents?. A literature search was performed the b-on electronic platform, we used the following keywords adolescen*, inflammatory bowel disease*, impact and quality of life, the timeframe between two thousand and eight (2008) and two thousand and thirteen (2013), not setting any language. To intersetar research articles the Boolean operator "AND" was used. This research was returned six hundred sixty-seven (667) results. The search was refined by descriptor (MeSH) inflammatory bowel diseases, and returned twenty-eight (28) results. Applied the inclusion and exclusion criteria, we selected six scientific articles. Analysed the results of each research paper, it is concluded that the quality of life of adolescents with inflammatory bowel disease have an impact on the biological, psychological and social dimension, especially physical health, self-image and functioning and school.